Technical efficiency and impact evaluation differentials between the adopters and non-adopters of Nerica in the six baseline states in Nigeria - Obayelu, A.E.; Adeoti, J.O.; Dontsop Nguezet, Paul M. (Slovak University of Agriculture in Nitra, 2017)
The study examined the adoption rate of New Rice for Africa (NERICA), technical efficiency differentials of production of these varieties between adopters and non-adopters and the determinants. It further analysed the impact of adoption of NERICA on area cultivated, output, yield, expenditure and total income of rice farmers in the NERICA baseline states in Nigeria. To achieve the objectives, it employed the descriptive statistics, stochastic production frontier and counterfactual outcomes framework of modern evaluation technique (the Local Average Treatment Effect) to analyse 621 rice farmers across the six NERICA baseline states in Nigeria in 2012. The findings show that NERICA adopters were more technically efficient than the non-adopters. In addition, adoption of NERICA was found to significantly increase the areas of land cultivated, output, yield, household expenditure, per capita household expenditure and total income among NERICA adopters by 1.2ha (p < 0.01), 1998.2kg (p< 0.01), 191.2kg/ha (p < 0.1), N13,222.63≈$66.4 (p< 0.05), N2,015.6≈$10.1 (p < 0.05) and N145,098.7 ≈$728.0 (p < 0.01) respectively despite their high level of inefficiency (39 percent) by the adopters. The positive impact of NERICA adoption on rice yields, poverty status measured by the per capita household expenditure and total farm income of farmers is a clear indication that NERICA has the potential to increase rice productivity, reduce poverty and food insecurity. NERICA adoption rate will rise if more farmers are aware of the varieties in the study. Farmers who had adopted, and government at all levels should therefore intensify their efforts to encourage others rice farmers possibly through the extension agents on the need to grow NERICA varieties so as to increase rice production level, reduce rice importation and ensure a sustainable rice production.